2015
DOI: 10.1515/ssr-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

From Preparation to Competitive Period in Soccer: Hematological Changes

Abstract: Hematological parameters affect the aerobic capacity which is considered as basic for technical and tactical development of soccer players. However, the hematological parameters such as hemoglobin (HBG), hematocrit (HCT), red blood cells (RBC), iron status and ferritin concentration, change throughout a season. Therefore, the current longitudinal study aimed to examine the changes of hematological parameters in professional soccer players throughout a 6-month period. The researchers examined 25 soccer players … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In fact, increases in hemoglobin levels are related to a greater aerobic performance due to the better oxygen transport capacity ( Otto et al, 2013 ). Several studies reported declines in hemoglobin levels in professional soccer players after periods of high-intensity activity ( Silva et al, 2008 ; Bekris et al, 2015 ). Given that, monitoring hemoglobin levels can be useful for assessing SSGs intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, increases in hemoglobin levels are related to a greater aerobic performance due to the better oxygen transport capacity ( Otto et al, 2013 ). Several studies reported declines in hemoglobin levels in professional soccer players after periods of high-intensity activity ( Silva et al, 2008 ; Bekris et al, 2015 ). Given that, monitoring hemoglobin levels can be useful for assessing SSGs intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed decreases in Hb and Ht values after periods of intense training or competition [6,7,26]. These declines are known as an adaptation to training and called sports pseudo-anemia [29,6].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that most common hematological measurements (e.g., plasma volume [PV], hemoglobin [Hb], hematocrit [Ht], and red blood cells [RBC] count) are linked to the development of aerobic capacity [7]. Previous research suggested that intensive physical stress affects PV and hematological parameters, which may negatively influence players’ physical performance [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the common influencers of aerobic fitness (e.g., ventilatory kinetics, cardiac process, neuromuscular status), other hematological and biochemical parameters assume a preponderant role in athletes’ performance [ 22 ]. However, there is incongruent evidence regarding the effects of acute and/or chronic training stimulus on hematological parameters, such as hemoglobin (Hb), red blood cells (RBC), and hematocrit (Ht) [ 23 ]. It seems that there is a trend to observe increases in the above-mentioned hematological parameters after a period of soccer training, especially during the preparation phase [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It seems that there is a trend to observe increases in the above-mentioned hematological parameters after a period of soccer training, especially during the preparation phase [ 24 ]. The Hb, RBC, and Ht are important hematological parameters since they are linked to the player’s aerobic capacity, which is one of the physical aspects most trained during the pre-season [ 23 , 25 ]. In the case of biochemical parameters, they represent an important role for the monitoring of an athlete’s responses to the training loads imposed [ 26 ].…”
Section: Introductionmentioning
confidence: 99%